Combination of Stimulated Thyroglobulin and Antithyroglobulin Antibody Predicts the Efficacy and Prognosis of 131I Therapy in Patients With Differentiated Thyroid Cancer Following Total Thyroidectomy: A Retrospective Study - Pan, Mengjiao; Li, Zhuyao; Jia, Meng; Lu, Xiubo (Frontiers in Endocrinology, 2022)
Background and purpose: To analyze the diagnostic ability of the combination of stimulated thyroglobulin (sTg) and anti-thyroglobulin antibody (TgAb) in predicting the efficacy and prognosis of radioactive iodine (131I) therapy (RAIT) in patients with differentiated thyroid carcinomas (DTCs) after total thyroidectomy (TT). Methods: This retrospective study comprised 409 DTC patients who underwent 131I treatment following TT in the First Affiliated Hospital of Zhengzhou University from January 2019 to August 2020 and they were followed up to November 2021. Patients were divided into the successful ablation and the unsuccessful ablation group based on the classification of the efficacy of RAIT in the 2015 American Thyroid Association guidelines. The clinical characteristics and the efficacy of the initial RAIT were evaluated. The cutoffs of pre-ablation sTg, sTg/ thyroid-stimulating hormone (TSH) ratio, and sTg×TgAb product were calculated to predict the efficacy of RAIT. Univariate and multivariate logistic regression analyses were used to identify the independent risk factors for unsuccessful ablation. Kaplan–Meier curves were used to estimate the prognostic value of sTg×TgAb product affecting progression-free survival (PFS). Results: The cohort consisted of 222 cases in the successful ablation group and 187 cases in the unsuccessful ablation group. Between the two groups, pre-ablation sTg, sTg/TSH ratio, and sTgTgAb product were significantly higher in the successful ablation group. The area under the curve (AUC) of the sTg×TgAb product was the highest among the above three factors. The cutoffs for the worse therapeutic effect of the initial RAIT in sTg, sTg/TSH ratio, and sTg×TgAb were ＞2.99ng/mL, ＞0.029mg/IU, and＞34.18, respectively. STg＞2.99 ng/mL, and sTg×TgAb product＞34.18 were independent risk factors for unsuccessful ablation. Patients with sTg×TgAb product＞34.18 had shorter PFS than that of patients with sTg×TgAb product≤34.18. In separate analyses of TgAb-negative and TgAb-positive subgroups, higher sTg×TgAb was both associated with a lower success rate of RAIT and a shorter PFS. Conclusion: STg×TgAb product predicted the efficacy and prognosis of 131I therapy for both TgAb-negative and TgAb-positive DTC patients before the initial 131I treatment following TT. Thus, it can be used as a clinical reference indicator for the surveillance of DTC patients.